A friend of mine solved the following exponential equation in the following way:


Since $\log_{4}8=\frac{3}{2}$, $4^{x+1}-(4^{2x})^{\frac{3}{2}})=0 \Leftrightarrow 4^{x+1}-4^{3x}=0$. Now that both $x$-terms are base 4, this equation is trivial to solve. However, I don't understand how that process can work. Is there any base to this process or was it just a lucky coincidence?

Note: I know how to solve that equation, I'm only asking if my friend's approach is valid or not

  • $\begingroup$ Yes, your friend's approach is valid $\endgroup$ – Omnomnomnom Jan 30 '17 at 19:45
  • $\begingroup$ @Omnomnomnom Interesting, can you point me to some resources/formulas for this? $\endgroup$ – imas145 Jan 30 '17 at 19:51

Well you have that $8=2^{3}=(\sqrt{4})^3=4^{3/2}$.Now as to why it works we have that $$a^{\log_a b}=b$$ Now plugging in $b=8$ we can write $$8=4^{\log_4 8}$$ And we have that $\log_4 8=\frac{3}{2}$ So we can write $8^{2x}$ as $(4^{3/2})^{2x}$. Your friends approach is correct.


Another, less convoluted way is to convert everything to base 2: $$ 0 = (2^2)^{x+1} - (2^3)^{2x} = 2^{2x+2} - 2^{6x}... $$

  • 3
    $\begingroup$ This doesn't answer the question being asked. $\endgroup$ – Omnomnomnom Jan 30 '17 at 19:46

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.